Conventionalism and structuralism in Madhyamaka and science - Holder, JP (2023)
This dissertation offers a novel reading of the 2nd century Indian Buddhist philosopher Nāgārjuna and explains how, having adopted his philosophical perspective, one may successfully navigate the contemporary scientific realism debate and explain how theories connect with reality. The view I ascribe to Nāgārjuna is that sentences proclaiming the existence or nonexistence of anything are conventions: statements which lack truth-values and should be accepted or rejected based on convenience. I call this ontological conventionalism. I argue that his methodology can be understood using certain Kantian ideas, and that that his form of metaphysics is compatible with even a very strict naturalistic stance. I also show that the French scientist and philosopher Henri Poincaré espoused ontological conventionalism. I argue that Poincaré’s phenomenal relationism can serve as an antirealist account of science that is compatible with Nāgārjuna’s philosophy. I further argue that an ontological conventionalist can make careful use of epistemic structural realism to explain the efficacy of theories (whether scientific, Buddhist, or otherwise). I do so by developing an original formulation of structural realism which revitalises (and goes beyond) Bertrand Russell’s original claim that all we know about even the observable world is its structure – an idea thought to have been defeated by M.H.A. Newman in 1928. It’s this form of ‘structural realism’ that I rely on to explain how an ontological conventionalist can account for the success of science without denying that scientific theories give us knowledge about the world beyond what is observable. I thus present both an antirealist and a realist route through which the success of science can be accounted for in ways consistent with Nāgārjuna’s philosophy.